Ketahanan Air Irigasi pada Wilayah Sungai di Indonesia - Waluyo Hatmoko; Radhika Radhika; Rendy Firmansyah; Anthon Fathoni (Balai Teknik Irigasi, 2017)
Water security is the community's ability to maintain sustainability in meeting water demands for various purposes and managing water-related disasters. The score of Asian countries water security indicator has been formulated and calculated by the Asian Development Bank (ADB). However water security at the river basin level, including irrigation water security, has not been assessed. Like other Asian countries, irrigation in Indonesia is the largest water user, therefore irrigation water security plays important role in water resources management. This paper formulates and calculates the water security for irrigation in all river basins in Indonesia. The computation method is adopted from ADB, and developed according to the conditions of data availability and characteristics of river basins in Indonesia, under the assumption of homogeneity within river basin. It is concluded that the irrigation water security in the river basin in Indonesia is generally in